2015
DOI: 10.1111/deci.12138
|View full text |Cite
|
Sign up to set email alerts
|

Keep Your Friends Close? Supply Chain Design and Disruption Risk

Abstract: In this article, we evaluate the relationship between supply chain design decisions and supply chain disruption risk. We explore two supply chain design strategies: (i) the dispersion of supply chain partners to reduce supply chain disruption risk versus (ii) the co-location of supply chain partners to reduce supply chain disruption risk. In addition, we assess supply chain disruption risk from three perspectives: the inbound material flow from the supplier (supply side), the internal production processes (int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 75 publications
(114 reference statements)
3
73
0
Order By: Relevance
“…Even recently, Habermann et al (2015) investigated supply chain disturbances in co-located and dispersed supply chain designs and found that co-location with suppliers is related to shorter duration of disruptions. However, the study of the effect of disturbances on supply chain design, and supply chain re-configuration as a disturbance mitigating strategy is relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Even recently, Habermann et al (2015) investigated supply chain disturbances in co-located and dispersed supply chain designs and found that co-location with suppliers is related to shorter duration of disruptions. However, the study of the effect of disturbances on supply chain design, and supply chain re-configuration as a disturbance mitigating strategy is relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…However, there should be other reasons that have not yet been investigated in detail. Examples include, but are not limited to, a firm's readiness (Macdonald & Corsi, 2013), relationships with suppliers (Grewal, Johnson, & Sarker, 2007), and supply chain complexity (Bode & Wagner, 2015;Habermann, Blackhurst, & Metcalf, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The response rate must have been a little higher but some of the e-mail addresses or contact information of respondents were either outdated or incorrect reducing the sample size less than 205. There are also research studies conducted with lower response rate but with valid justifications (Habermann et al 2015). Hence, 35% response rate is considered as a valid rate for evaluating survey data.…”
Section: Survey Findings and Discussionmentioning
confidence: 99%